2004
DOI: 10.1002/chem.200400836
|View full text |Cite
|
Sign up to set email alerts
|

“Bent Bonds” between Bismuth and Carbon Atoms as a Result of CH Activation in MoBi Complexes

Abstract: The reaction of molybdocenedihydride with two equivalents of [Bi(OtBu)(3)] proceeds via alcohol elimination and provides the compound [Cp(2)Mo{Bi(OtBu)(2)}(2)] (1), which contains two Mo--Bi metal bonds, in good yields. If the two reagents are employed in a 1:1 ratio continuative condensation reactions occur. These initially lead to [{Cp(2)Mo}(2){mu-Bi(OtBu)}(2)] (2), which, however, is very unstable in solution and decomposes via additional alcohol elimination: Complex-induced proximity effects facilitate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 20 publications
4
32
0
1
Order By: Relevance
“…The Bi-C bonds are surprising in that they are bent out of the plane of the cyclopentadienyl rings by approximately 40 • , suggesting a non-linear overlap between Bi and C orbitals. A theoretical investigation into this system showed the two isomeric products to be close in energy, with the unsymmetrical isomer slightly favoured [77]. The calculated Wiberg bond index between the bismuth and carbon centres suggests a relatively strong interaction, with natural bond order analyses indicating 2c-2e bonds polarised towards carbon.…”
Section: "Bent" Bismuth-carbon Bondsmentioning
confidence: 91%
See 1 more Smart Citation
“…The Bi-C bonds are surprising in that they are bent out of the plane of the cyclopentadienyl rings by approximately 40 • , suggesting a non-linear overlap between Bi and C orbitals. A theoretical investigation into this system showed the two isomeric products to be close in energy, with the unsymmetrical isomer slightly favoured [77]. The calculated Wiberg bond index between the bismuth and carbon centres suggests a relatively strong interaction, with natural bond order analyses indicating 2c-2e bonds polarised towards carbon.…”
Section: "Bent" Bismuth-carbon Bondsmentioning
confidence: 91%
“…Early research into bismuth-molybdenum species showed that the reaction of BrBiMe 2 and the sodium molybdate Na[Cp(CO) 3 Mo] did not result in the expected dimethyl derivative but instead in twofold substituted [{Cp(CO) 3 Both the bimetallic and trimetallic species exist for molybdenum, and are in fact in equilibrium in solution meaning that stoichiometric control is essential for high-yielding synthesis of either target [77][78][79]. The concentration of BiCl 3 is the controllable factor, its addition resulting in redistribution reactions in solution, in accordance with the equilibria.…”
Section: Molybdenum Compoundsmentioning
confidence: 99%
“…Complex 19 contains two doubly deprotonated cyclopentadienyl ligands, η 5 -μ 4 -C 5 H 4 , deprotonated in the 1,2-positions. Such selective multiple deprotonations of cyclopentadiene are rare and have been observed in group 8 and ferrocene compounds but only in the form of 1,3-deprotonations (Clegg et al 2001, Andrikopoulos et al 2004, Roggan et al 2005 . DFT calculations on the Lu-Re bond in 19 revealed 81 % of the population as Re character and 8 % belonging to each of the Lu atoms.…”
Section: Lanthanide-transition Metal Complexesmentioning
confidence: 97%
“…Upon cooling to 253 K signal separation occurs and for the CH 2 group (typical) geminal [18] The here observed selective 1,2-bis-deprotonation of one Cp ring of a metallocene is unusual. [19] The three Lu ions of the central structural element form an approximately equilateral triangle with two sides being bridged by C 2 Re triangles.…”
mentioning
confidence: 99%